2023
DOI: 10.1038/s41396-023-01447-4
|View full text |Cite
|
Sign up to set email alerts
|

High speciation rate of niche specialists in hot springs

Abstract: Ecological and evolutionary processes simultaneously regulate microbial diversity, but the evolutionary processes and their driving forces remain largely unexplored. Here we investigated the ecological and evolutionary characteristics of microbiota in hot springs spanning a broad temperature range (54.8–80 °C) by sequencing the 16S rRNA genes. Our results demonstrated that niche specialists and niche generalists are embedded in a complex interaction of ecological and evolutionary dynamics. On the thermal toler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 81 publications
(96 reference statements)
0
7
0
Order By: Relevance
“…This raises a fascinating question about the coexistence of bacterial taxa within generalists or specialists, which – for over 50 years – has been a major issue in ecological theory, where the number of species often appears to exceed the available niches, a phenomenon commonly known as ‘The paradox of the plankton’ (Hutchinson, 1961). The coexistence of bacterial taxa between generalists and specialists can be influenced by different strategies, such as intra‐specific variation, dormancy potential and evolutionary potential (He et al, 2023; Xu, Luo, et al, 2022; Yang et al, 2023). However, bacterial taxa within generalists or specialists have similar ecological strategies, but how they coexist remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This raises a fascinating question about the coexistence of bacterial taxa within generalists or specialists, which – for over 50 years – has been a major issue in ecological theory, where the number of species often appears to exceed the available niches, a phenomenon commonly known as ‘The paradox of the plankton’ (Hutchinson, 1961). The coexistence of bacterial taxa between generalists and specialists can be influenced by different strategies, such as intra‐specific variation, dormancy potential and evolutionary potential (He et al, 2023; Xu, Luo, et al, 2022; Yang et al, 2023). However, bacterial taxa within generalists or specialists have similar ecological strategies, but how they coexist remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…We note that many thermophilic habitat generalists have been identified before, even along strong environmental gradients, e.g. (21,(60)(61)(62), so an absence of habitat generalists in our data set is surprising, although many thermophiles tend to be habitat specialists for temperature (20,45,63).…”
Section: Discussionmentioning
confidence: 74%
“…Specifically, we found that the microbial assemblage strategies of both abundant and rare taxa were influenced by environmental factors, consequently formed distinct geographical patterns across the saline lake region of northwestern China. While several studies focused on generalists and specialists in microbial communities 54,59,60 , our study investigated abundant and rare taxa following the methods used in a hot spring study 61 to dissect the ecological roles of microbial communities under different niches. We also uncovered that rare taxa act as keystone species in the communities, exhibiting wide adaptation across a large geographical scale.…”
Section: Discussionmentioning
confidence: 99%